UPGRADING SKILL GURU MTSN 2 LANGKAT DALAM PENYUSUNAN MODUL AJAR DAN PROFIL PELAJAR PANCASILA - Enda Lovita Pandiangan; Satria Wiguna; Muhammad Sulaiman; Maulida Khairunnisa (Universitas Islam Malang, 2023)
The inability of educators at the MTSN 2 Langkat school to understand changes to the independent learning curriculum has an impact on the inaccuracy of preparing learning modules that are in accordance with the changing curriculum. Many terms in the new curriculum require a new understanding and a change in learning focus which focuses more on developing student competencies and a sustainable learning process. The aim of this activity is to facilitate teachers and improve skills at MTsN 2 Langkat in designing learning modules that are in accordance with the Merdeka Curriculum, so that the learning process can be planned effectively and optimally. The methods used in this activity are socialization, education, training and evaluation of the creation of teaching modules. The implementation of this community service has achieved an increase in the soft skills of educators in compiling teaching modules for the independent learning curriculum at MTSN 2 Langkat. The results of the implementation of PKM activities show that the training activities ran smoothly and the activity participants were enthusiastic in participating in the training. The positive benefits obtained from this activity include increased understanding of the independent learning curriculum as well as new knowledge related to preparing learning modules that are in accordance with the latest curriculum. This activity received good interest from partners because the material was easy to understand, right on target and the activity duration was adequate.